2010
DOI: 10.1510/icvts.2010.232546
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and prognosis of initial pericardiocentesis in the primary management of malignant pericardial effusion

Abstract: We retrospectively reviewed the records of 100 patients with malignant disease and symptomatic pericardial effusion initially treated with pericardiocentesis at the National Cancer Institute of Mexico between 1985 and 2009. We analyzed predictive factors for recurrence of pericardial effusion by bi- and multivariate analyses. The group comprised 74 women and 26 men. Twenty patients had developed malignant pericardial effusion at the time of primary cancer diagnosis. Recurrence rate after pericardiocentesis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 13 publications
1
29
1
3
Order By: Relevance
“…2). Our findings were compatible with some prior studies (Celik et al 2012, Cullinane et al 2004, Rousseau-Bussac et al 2014, Tsang et al 2000, Apodaca-Cruz et al 2010). …”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…2). Our findings were compatible with some prior studies (Celik et al 2012, Cullinane et al 2004, Rousseau-Bussac et al 2014, Tsang et al 2000, Apodaca-Cruz et al 2010). …”
Section: Discussionsupporting
confidence: 94%
“…Lung cancer has the worst outcomes in patients with MPE (Tsang et al 2000, Celik et al 2012, Cullinane et al 2004, Apodaca-Cruz et al 2010, Rousseau-Bussac et al 2014. Male sex, positive effusion cytology for malignancy, lung cancer, and tamponade or hemodynamic collapse are independently associated with poor survival for MPE (Tsang et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsang TS et al 14 evaluated the various treatment strategies for primary and secondary management of malignancyrelated pericardial effusions and concluded that for both the primary and secondary management of pericardial effusion in patients with malignancies, echocardiographically guided pericardiocentesis with extended catheter drainage appears to be safe and effective procedure. Apodaca-Cruz A et al 15 retrospectively analyzed patient's records that were affected with malignant disease and symptomatic pericardial effusion initially treated with pericardiocentesis and reported that recurrence rate after pericardiocentesis was 33% and concluded that pericardial window can be considered as a secondary strategy for recurrence, with high effectiveness of the primary management of pericardial effusion with pericardiocentesis in oncologic patients.…”
Section: Discussionmentioning
confidence: 99%
“…This was highlighted by the minimal mortality and morbidity reported in the present systematic review, especially in centres routinely employing echocardiographic guidance (table 3). 19 21 22 Nonetheless, despite its relative safety, isolated pericardiocentesis was associated with a relatively high incidence of 38.3% for recurrent effusions.…”
Section: Discussionmentioning
confidence: 99%